Answer: 1.4
Step-by-step explanation: First, swap the sides of the equation so that the one with the variable can be in front.
So, its 2y=2.8
To solve this, you simply divide both sides of the equation by 2.
2 divided by 2 is 0. That leaves you with the y by itself. Then, 2.8 divided by 2 is 1.4
So, y=1.4
Answer:
B.
Step-by-step explanation:
The answer is B
5:2:11=15:6:33
Multiply by 6/2=3
9514 1404 393
Answer:
D
Step-by-step explanation:
Solve x = f(y) for y.
x = ∛(y/9) -4
x +4 = ∛(y/9) . . . . . add 4
(x +4)³ = y/9 .. . . . . cube
9(x +4)³ = y . . . . . . multiply by 9
The inverse function is ...
f⁻¹(x) = 9(x +4)³ . . . . . matches the last choice